THE CONSTITUTIONALITY OF PIX AMENDMENTS: ANALYSIS OF THE DELIMITATION OF THE ROLES OF THE EXECUTIE AND LEGISLATIVE BRANCHES IN BUDGET EXECUTION (ESMAT Magazine, 2025)
The dispute between the Legislative and the Executive for the allocationof the budget is intensified by parliamentary amendments, with voluntary transfers,known as PIX amendments, an agile modality, incresingly used by parliamentarian, toallocate resources to their electoral bases. Introduced by article 166- A OF THE FederalConstitucional of 1988, these amendments allow the direct transfer of federal resourcesto states, Federal District and Municipalities, without the need to be linked to specificprojects and without the formality of agréments. The reserch aims to analyze theconstitucionality of the execution of these amendments considering the delimitation ofthe roles of ?Executive and the Legislative. The reerch hypotheses include greaterfreedom in the Legislative Branch in the preparation of the budget, incresing theautonomy of subnational entities in the execution of public policies, the lack of transparency and fiscal control, the eleitoral imbalance, the governance crises, and thepossibility of resource allocation misaligned with the PPA (four year plan),compromising the mandatory budget. The research uses the hypothetical-deductivemethod, with tecnical procedures of bibliographic, jurisprudencial reserach and datacollection, higlighting the need for advances uin transparency, oversigth, andefectiveness in the application of publica resources.
Keywords: PIX Amendments; Unconstitutionality; Transparency; Efficiency